ANRIL lncRNA triggers efficient therapeutic efficacy by reprogramming the aberrant INK4-hub in melanoma. Issue 1 (10th October 2016) - Xu, Shiqiong; Wang, Huixue; Pan, Hui; Shi, Yingyun; Li, Tianyuan; Ge, Shengfang; Jia, Renbing; Zhang, He; Fan, Xianqun
Highlights: We showed a novel "domino effect-like" anti-melanoma therapeutic approach . Endogenously auto-corrected aberrant INK4- hub by suppression of ANRIL lncRNA. This approach reduced the tumor metastatic capacity and tumor formation. Abstract: Melanoma is an extremely aggressive disease with rapid progression, high metastatic potential and recurrence. Simultaneous correction of multiple tumor-specific gene abnormalities has become an attractive approach for developing therapeutics to treat melanoma. To potentiate anti-melanoma activity, we tested a "domino effect-like" therapeutic approach by uniquely targeting one defect and automatically triggering the endogenous corrections of other defects. Using this strategy, in a suspicious INK4b–ARF–INK4a gene cluster at chromosome 9p21, aberrant INK4a and INK4b defects were simultaneously endogenously auto-corrected after targeting the suppression of abnormal ANRIL lncRNA. In cell culture, this treatment significantly reduced the tumor metastatic capacity and tumor formation compared with absence of treatment. In animals harboring tumor xenografts, this therapeutic approach significantly inhibited tumor growth and reduced the tumor weight. Our results reveal a novel therapeutic strategy that significantly potentiates anti-melanoma efficiency by reprogramming the aberrant INK4 -hub.